DEVELOPING THE POTENTIALS OF AFRICA THROUGH GIRL- CHILD EDUCATION: A CASE STUDY OF NIGERIA AND CAMEROON - Olanrewaju, Ahmed (African Journal of Educational Management, 2021)
Education is fundamental to poverty reduction and it equips individuals to contribute immensely to the socio-economic development of society. However, studies have revealed a wide gap in gender enrolment in primary education in Sub-Saharan Africa, Nigeria and Cameroon inclusive caused by gender issues and socio-cultural beliefs among other practices, as well as deeper forces that extend beyond the boundaries of educational systems. This study therefore investigated the trends in girl-child participation in primary education in Nigeria and Cameroon and the causes of disparity. The study adopted descriptive survey design using the ex-post facto method. Two research questions and two hypotheses were raised in the study. The instruments used for this study were the Parent’s Questionnaire on Girl-Child Participation in Primary Education (PQGPPE) and Questionnaire for Street Girls of Primary School Age (QSGPSA). Data collected were analysed using chi-square, T-test and descriptive statistics. There is high perception of parents in Nigeria and Cameroon (Nigeria; Weighted Average = 2.79, Cameroon; weighted Average= 2.94). There is no significant difference in the responses of street girls and parents on factors militating against girl-child education. Hence, hypotheses 2a and 2b are accepted. T-test comparison of Girl-Child Enrolment shows that the girls’ enrolment in Cameroon is higher ( = 45.6) than that of Nigeria ( = 40.7) at (t = 12.33; df =30; p <.05). Girl-child participation in primary education in both countries is not encouraging and socio-cultural and economic factors are predominant causes hindering their accessibility. Therefore, cultural practices like early marriage, preference for boy-child education, among others should be discouraged by governments of both countries.